Common Failings: How Corporate Defaults Are Correlated - DAS, SANJIV R.; DUFFIE, DARRELL; KAPADIA, NIKUNJ; SAITA, LEANDRO (Journal of Finance, 2007)
ABSTRACT We test the doubly stochastic assumption under which firms' default times are correlated only as implied by the correlation of factors determining their default intensities. Using data on U.S. corporations from 1979 to 2004, this assumption is violated in the presence of contagion or “frailty” (unobservable explanatory variables that are correlated across firms). Our tests do not depend on the time‐series properties of default intensities. The data do not support the joint hypothesis of well‐specified default intensities and the doubly stochastic assumption. We find some evidence of default clustering exceeding that implied by the doubly stochastic model with the given intensities.